The family in Greek history - Patterson, Cynthia (Harvard University Press, 1998)
The Family, Cynthia Patterson demonstrates, played a key role in the political changes that mark the history of ancient Greece. From the archaic society portrayed in Homer and Hesiod to the Hellenistic age, the private world of the family and household was integral with and essential to the civic realm. This is an understanding that fits the Athenian concept of the city as the highest form of family. The suppression of the cities with the ascendancy of Alexander's empire led to a new resolution of the relationship between public and private authority: the concept of a community of households, which is clearly exemplified in Menander's plays. Undercutting hitherto common interpretations of Greek experience as evolving from clan to patriarchal state, Patterson's insightful analysis sheds new light on the role of men and women in Greek culture.